A semi-alternating algorithm for solving nonconvex split equality problems. (18th November 2021) - Moudafi, Abdellatif
Abstract: In this paper, we propose an iterative method for solving split equality problems in the nonconvex setting. Relying on the associated penalized optimization formulation, we study a relevant iterative algorithm, which is nothing else than a generalized CQ-algorithm, and prove that its global convergence is guaranteed in the nonconvex setting under mild conditions on the problems data. Then, some remarks are also mentioned.